2014
DOI: 10.1163/15685306-12341325
|View full text |Cite
|
Sign up to set email alerts
|

Dog at My Feet: A Moment of Identity Construction within Dissertation Acknowledgements

Abstract: Human-animal studies (has) is a legitimate and multidisciplinary academic endeavor. In the last three decades, there has been a proliferation of articles revealing multiple ways of knowing about the human-animal relationship. This paper, informed by social psychological theories, turns the mirror upon new researchers as they emerge as professional selves into academia. Post-graduate students engage multiple and sometimes contradicting identities throughout their candidatures. The unit of analysis is the disser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Existing research has shown that writers from soft sciences tend to use more stance markers (e.g., modal verbs, hedges), write in longer sentences, and acknowledge more emotional and social support from family members and friends than writers from hard sciences in acknowledgment writings (Chan, 2015;Giannoni, 2002;Hyland, 2003;Hyland & Tse, 2004). These studies have mainly approached the writing style of dissertation acknowledgments by explicating a three-tier rhetorical move structure of reflecting (recounting personal research experience), thanking (crediting individuals who helped), and announcing (acknowledging responsibilities and inspirations) (Billany, 2014;Hyland, 2003Hyland, , 2004Yang, 2012). Some others investigated the expression of stance in dissertation acknowledgments by examining their lexico-grammatical devices such as modal and semi-modal verbs, adverbs, and complement clauses.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has shown that writers from soft sciences tend to use more stance markers (e.g., modal verbs, hedges), write in longer sentences, and acknowledge more emotional and social support from family members and friends than writers from hard sciences in acknowledgment writings (Chan, 2015;Giannoni, 2002;Hyland, 2003;Hyland & Tse, 2004). These studies have mainly approached the writing style of dissertation acknowledgments by explicating a three-tier rhetorical move structure of reflecting (recounting personal research experience), thanking (crediting individuals who helped), and announcing (acknowledging responsibilities and inspirations) (Billany, 2014;Hyland, 2003Hyland, , 2004Yang, 2012). Some others investigated the expression of stance in dissertation acknowledgments by examining their lexico-grammatical devices such as modal and semi-modal verbs, adverbs, and complement clauses.…”
Section: Introductionmentioning
confidence: 99%